2006
DOI: 10.1097/00001888-200601000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Duty-Hour Restrictions and the Work of Surgical Faculty: Results of a Multi-Institutional Study

Abstract: Duty-hour restrictions have been consequential for the work of surgical faculty. Faculty should not be overlooked in future studies of duty-hour restrictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 7 publications
2
31
0
2
Order By: Relevance
“…The degree of satisfaction that faculty members derive from these different tasks varies, and individuals may not always have the opportunity to focus on the areas that they view as most personally meaningful. 10,12,[15][16][17][18][19] To our knowledge, no studies have evaluated the relationship between career fit (the extent to which an individual is able to focus their effort on the aspect of work that they find most meaningful) and faculty burnout.…”
Section: He Practice Of Medicinementioning
confidence: 99%
“…The degree of satisfaction that faculty members derive from these different tasks varies, and individuals may not always have the opportunity to focus on the areas that they view as most personally meaningful. 10,12,[15][16][17][18][19] To our knowledge, no studies have evaluated the relationship between career fit (the extent to which an individual is able to focus their effort on the aspect of work that they find most meaningful) and faculty burnout.…”
Section: He Practice Of Medicinementioning
confidence: 99%
“…One study of cardiothoracic surgical experience showed that overall experience with coronary artery bypass grafting significantly decreased in the post-duty hour time period (from 148 cases to 110 cases combining all years of residency). 82 Another study of abdominal trauma surgery 42 found that the overall number of operative procedures per graduating resident in the last 2 years of their residency did not differ between the pre-and post-duty hour periods; however, there was a significant decrease in the number of advanced emergency abdominal cases (51 versus 31) and an increase in the number of basic abdominal cases 83 One theme identified in the analysis of the interviews was that routine work was being shifted from residents to faculty. For example, they reported that residents only come to the operating room, while the faculty provided the preoperative and postoperative care.…”
Section: Standardized Testsmentioning
confidence: 99%
“…16,17,21,22 Despite the perception of increased faculty work hours, several studies have found no significant change in the ac-tual number of faculty work hours or cases before and after the implementation of the work-hours reform. 16,17,21,23 Interestingly, in one study, almost half of surgeons believed that they were working more even though their actual work hours did not change, and this perception was especially prominent among general surgeons. 16 These perceptions of increased workload and diminished job satisfaction may be related to changes in the composition of faculty workload following work-hours reforms (eg, less time in administrative tasks, meetings, educational activities, and research, and increased patient care duties).…”
mentioning
confidence: 99%